Effects of ewe feeding system (grass vs concentrate) on milk fatty acid composition - Valvo M.A.; Bella M.; Scerra M.; Biondi L. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The aim of this work was to investigate whether and how the feeding system could affect ewe milk fatty acids. Twenty pregnant Comisana ewes were divided into two groups of ten one month before lambing and allowed two different feeding systems: Pasture group (P) grazed on a vetch pasture; Stall group (S) was given hay, a commercial concentrate and a mixture of barley and faba bean. After lambing, individual milk samples were taken weekly and analysed for fatty acid composition. The trial went on for 38 days. Milk from P ewes was poorer in lauric (C12:0), myristic (C14:0) and palmitic (C16:0) acids than milk from S ewes (P < 0.05, P < 0.001 and P
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)